Affective variables, parental involvement and competence among South Korean high school learners of English - Morris, Annie; Lafontaine, Marc; Pichette, François; de Serres, Linda (Studies in Second Language Learning and Teaching, 2013)
This study investigated the relationships between various affective variables and two measures of competence in English, for 190 South Korean high school students. A 55-item questionnaire was used to measure attitudes (Attitudes toward English Speakers and their Communities and Attitudes toward the English-speaking Culture), motivation (Motivational Intensity, Desire to Learn and Attitudes toward the Learning of English), amotivation, parental involvement (Active Parental Encouragement, Passive Parental Encouragement and Parental Pressure), parental disinterest and students’ competence in L2 (English- EXAM and English-SELF). Pearson product-moment coefficients indicate that active and passive forms of parental encouragement correlate with motivationto learn, as conceptualized by Gardner (1985, 2010), as well as with parental pressure, which suggests that South Korean students report undergoing forms of pressure when their parents actively or passively encourage them. Furthermore, the obtained correlations of the active and passive forms of encouragement with different variables suggest that the two forms represent two distinct concepts. While parental disinterest correlated negatively with motivational variables, parental pressure correlated only with motivational intensity, and only weakly. Therefore, parental pressure seems not to interact significantly with participants’ attitudes, motivation and competence. Multiple linear regression analyses confirm the importance of motivation to learn for students' L2 competence.